ARE WE SAFE ANALYSTS? Cisgender Countertransferential Fantasies in the Treatment of Transgender Patients - Porchat, Patricia [UNESP]; Santos, Beatriz (Guilford Publications, 2021)
The authors examine the impact of countertransference in two clinical cases of transgender patients treated by two cisgender analysts who are accustomed to receiving nonconforming gender patients in France and Brazil. The context is that of contemporary views of transphobic countertransference reactions, specifically the work of Griffin Hansbury, who describes these reactions in terms of “unthinkable anxieties.” Like other theorists with expanding notions of countertransference, the authors view transphobia in analysis as an “instrument of research” and consider how taking responsibility for the transference is particularly relevant in respect to clinical cases that also reflect societal changes. Following the authors’ case presentations, they identify four different fantasies and countertransferential reactions that sprang from their efforts to be safe analysts or, in other words, analysts concerned about the perpetuation of discrimination, violence, and oppression that may have guided their work.
Keywords: Clinical case; Counter transference; Gender experience; Systemic violence; Transgender